2010
DOI: 10.3917/popu.1002.0273
|View full text |Cite
|
Sign up to set email alerts
|

Les changements professionnels en France autour de la séparation conjugale

Abstract: Bonnet Carole et al., « Les changements professionnels en France autour de la séparation conjugale »,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
2
0
3
Order By: Relevance
“…Source: Emploi en continu 2003-2012 surveys (INSEE), author's calculations. (BONNET et al, 2010) and, if necessary, to participate in education offered by an employment agency in order to prepare their re-integration into the labour market as well as possible. This relationship between a separation and access to education offered by an employment agency, however, seems to be conditioned on factors relating to childcare: the positive influence of the break-up of a couple formed with an employed person is observed only for women who do not obtain custody of their children and men who, on the contrary, do have custody of them.…”
Section: Change In Conjugal Situation and Access To Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Source: Emploi en continu 2003-2012 surveys (INSEE), author's calculations. (BONNET et al, 2010) and, if necessary, to participate in education offered by an employment agency in order to prepare their re-integration into the labour market as well as possible. This relationship between a separation and access to education offered by an employment agency, however, seems to be conditioned on factors relating to childcare: the positive influence of the break-up of a couple formed with an employed person is observed only for women who do not obtain custody of their children and men who, on the contrary, do have custody of them.…”
Section: Change In Conjugal Situation and Access To Educationmentioning
confidence: 99%
“…4 In France, Sébastien GOSSIAUX and Patrick POMMIER (2013) showed that, based on the Adult Education Survey (AES) in 2012, family responsibilities are the obstacle most often cited by individuals (34% of cases). In addition, considering the broader literature on the links between labour supply and family events, many studies point out that births (PAILHÉ, SOLAZ, 2007), a child's entry into the public school system (MOSCHION, 2012;THÉVENON, 2009) and couple break-ups (BONNET et al, 2010) have an important impact on people's career paths and are therefore likely to influence their educational prospects.…”
mentioning
confidence: 99%
“…Le tableau 2 montre une corrélation entre séparation et participation aux formations proposées par un organisme de placement, mais uniquement dans le cas où le conjoint est actif occupé au moment de la rupture : les individus qui se séparent d'un conjoint en emploi ont plus de chances de participer à une telle formation que ceux qui ne se séparent pas (1,53 fois plus de chances pour les femmes et 1,77 fois plus de chances pour les hommes). Ces résultats peuvent être rapprochés de ceux de BONNET et al (2010) sur l'offre de travail. La séparation d'un conjoint en emploi est susceptible d'engendrer une baisse importante du niveau de vie pour les individus inactifs et chômeurs qui disposent de ressources propres faibles au sein du couple.…”
Section: Femmesunclassified
“…La séparation d'un conjoint en emploi est susceptible d'engendrer une baisse importante du niveau de vie pour les individus inactifs et chômeurs qui disposent de ressources propres faibles au sein du couple. Ces derniers peuvent alors être incités à réintégrer un emploi afi n de maintenir leur revenu (BONNET et al, 2010) et participer le cas échéant à une formation proposée par un organisme de placement afi n de préparer au mieux leur réinsertion sur le marché du travail. Cette relation entre séparation et accès aux formations proposées par un organisme de placement semble cependant conditionnée par les éléments relatifs à la garde des enfants : l'infl uence positive de la dissolution d'une union formée avec un individu en emploi n'est observée que pour les femmes qui n'obtiennent pas la garde de leurs enfants et pour les hommes qui, au contraire, en ont la garde.…”
Section: Femmesunclassified
“…Les éventuelles différences observées sont alors imputables à la mise en place de la réforme. Les méthodes d'appariement (voir Brodaty et al 2007 ;Givord, 2010 ;Bonnet et al, 2010) sont bien adaptées pour construire ce groupe témoin en fonction des caractéristiques observables 8 (encadré 3).…”
Section: Dossierunclassified